Antiangiogeneic Strategies in Mesothelioma - Nowak, Anna K.; Brosseau, Solenn; Cook, Alistair; Zalcman, Gérard (Frontiers in Oncology, 2020)
There is a strong rationale for inhibiting angiogenesis in mesothelioma. Vascular endothelial growth factor (VEGF) is an autocrine growth factor in mesothelioma and a potent mitogen for mesothelial cells. Further, the abnormal tumour vasculature promotes raised interstitial pressure and hypoxia, which may be detrimental to both penetration and efficacy of anticancer agents. Antiangiogenic agents have been trialled in mesothelioma for close to two decades, with early phase clinical trials testing vascular targeting agents, the VEGF-A targeting monoclonal antibody bevacizumab, and numerous tyrosine kinase inhibitors, many with multiple targets. None of these have shown efficacy which has warranted further development as single agents in any line of therapy. Whilst a randomised phase II trial combining the multitargeted tyrosine kinase inhibitor nintedanib with platinum/pemetrexed chemotherapy was positive, these results were not confirmed in a subsequent phase III study. The combination of cisplatin and pemetrexed with bevacizumab, in appropriately selected patients, remains the only anti-angiogenic combination showing efficacy in mesothelioma. Extensive efforts to identify biomarkers of response have not yet been successful.